2002
DOI: 10.1080/10284150290032012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aged Garlic Extract on Caspase-3 Activity, In Vitro

Abstract: In neurodegeneration, such as Alzheimer's disease (AD), apoptosis results in the loss of valuable neurons. A key mechanism in apoptosis is the activation of caspase-3. Caspase-3 activity first becomes detectable early in apoptosis, continues to increase as cells undergo apoptosis, and rapidly declines in late stages of apoptosis. Its activity is an early marker of cells undergoing apoptosis. Caspase-3 catalyzes the formation of beta-amyloid peptide, a hallmark of AD. The purpose of the study was to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…61 Surprisingly, Sarikaya and Gülçin proved that serotonin possess antioxidant and radical scavenging capacity by different in vitro methodologies. 62 Subsequently, in the current study, increased serotonergic activity could be considered as a compensatory mechanism to scavenge free radicals generated by tramadol, cannabis and their concurrent abuse.…”
Section: Discussionmentioning
confidence: 99%
“…61 Surprisingly, Sarikaya and Gülçin proved that serotonin possess antioxidant and radical scavenging capacity by different in vitro methodologies. 62 Subsequently, in the current study, increased serotonergic activity could be considered as a compensatory mechanism to scavenge free radicals generated by tramadol, cannabis and their concurrent abuse.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that garlic has beneficial effects in animals, including antioxidant, antiviral, and antifungal activities (Harris et al, 2001;Jackson et al, 2002). Previous research has suggested that these functions are mainly attributed to the bioactive components present in garlic, including sulfur-containing compounds, such as alliin, allicin, and diallyl sulfides (Amagase et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…16) To test the possible involvement of caspase-3 in ST-induced apoptosis and the inhibition by sauchinone, we measured the caspase-3 activity of C6 cells treated with ST in the presence or absence of sauchinone by measuring fluorescence generated from proteolytic cleavage of Ac-DEVD-AFC (50 mM). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…14,15) Both in vitro and in vivo evidence implicates caspase-3 as an important factor in neuronal apoptosis, especially under pathologic conditions. 16) Saururus chinensis (LOUR.) BAILL.…”
mentioning
confidence: 99%